2003
DOI: 10.1128/mcb.23.22.8233-8245.2003
|View full text |Cite
|
Sign up to set email alerts
|

Neurons Expressing the Highest Levels of γ-Synuclein Are Unaffected by Targeted Inactivation of the Gene

Abstract: Homologous recombination in ES cells was employed to generate mice with targeted deletion of the first three exons of the ␥-synuclein gene. Complete inactivation of gene expression in null mutant mice was confirmed on the mRNA and protein levels. Null mutant mice are viable, are fertile, and do not display evident phenotypical abnormalities. The effects of ␥-synuclein deficiency on motor and peripheral sensory neurons were studied by various methods in vivo and in vitro. These two types of neurons were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(111 citation statements)
references
References 57 publications
3
106
0
2
Order By: Relevance
“…Our studies show no phenotypic or histological differences in the inner ears of the wild-type vs. the knockout mice, while ABR thresholds and otoacoustic emissions also are unchanged in the knockout mouse through P21. This follows prior studies on this same mouse, in which no difference was observed in the number of neurons between wild-type and null mutant animals in several brain stem motor nuclei, in lumbar dorsal root ganglia, and in the trigeminal ganglion (Ninkina et al 2003). Lack of clear morphological and phenotypic differences were similarly observed in the CNS of α-synuclein null mutant mouse (Abeliovich et al 2000;Cabin et al 2002).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Our studies show no phenotypic or histological differences in the inner ears of the wild-type vs. the knockout mice, while ABR thresholds and otoacoustic emissions also are unchanged in the knockout mouse through P21. This follows prior studies on this same mouse, in which no difference was observed in the number of neurons between wild-type and null mutant animals in several brain stem motor nuclei, in lumbar dorsal root ganglia, and in the trigeminal ganglion (Ninkina et al 2003). Lack of clear morphological and phenotypic differences were similarly observed in the CNS of α-synuclein null mutant mouse (Abeliovich et al 2000;Cabin et al 2002).…”
Section: Discussionsupporting
confidence: 61%
“…3). Prior work has shown no obvious phenotypic changes in the γ-synuclein null mouse (Ninkina et al 2003). As shown by Figure 5, we could not identify any morphologic changes in the organ of Corti in the knockout compared to the wild-type mouse; organ of Corti histology, outer and inner hair cell numbers, and spiral ganglion cell numbers were normal and identical in each zygosity (only wild-type and knockouts are shown in Figure 5).…”
Section: γ-Synuclein Null-mutant Micementioning
confidence: 71%
See 1 more Smart Citation
“…Production, genotyping, and initial characterization of γ-synucleinnull mutant mice on a C57Bl6J genetic background have been described previously (4). The colony was maintained by backcross breeding, and intercrosses were used for production of experimental cohorts (details provided in SI Methods).…”
Section: Methodsmentioning
confidence: 99%
“…To date, no clear cellular role is attributed to γ-synuclein, and ablation of γ-synuclein causes only minor changes in the nervous system (4)(5)(6)(7). Recently, we and others have reported high levels of γ-synuclein expression in adipose tissue of humans and other mammals (8,9).…”
mentioning
confidence: 99%